2000
DOI: 10.1001/archinte.160.18.2835
|View full text |Cite
|
Sign up to set email alerts
|

The Gaucher Registry

Abstract: The Gaucher Registry permits a comprehensive understanding of the clinical spectrum of GD because of the uniquely large sample size. The Registry will be useful in evaluating the effects of specific therapies in GD and the possible influences of environment, ethnicity, and genotype on the natural history of the disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
116
1
5

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 472 publications
(131 citation statements)
references
References 19 publications
9
116
1
5
Order By: Relevance
“…Although a previous report of the International Collaborative Gaucher Group (ICGG) Gaucher Registry data noted that most affected people manifest GD in childhood, the clinical and demographic data for childhood GD were not separately analyzed. 8 This study analyzes data from the ICGG Gaucher Registry to characterize the manifestations at the time of diagnosis of a large population of children and adolescents with nonneuronopathic GD. This description of pediatric nonneuronopathic GD should increase the recognition and earlier diagnosis of this condition in childhood, allowing for the initiation of treatment before the development of severe morbidity or irreversible disease complications.…”
Section: Discussionmentioning
confidence: 99%
“…Although a previous report of the International Collaborative Gaucher Group (ICGG) Gaucher Registry data noted that most affected people manifest GD in childhood, the clinical and demographic data for childhood GD were not separately analyzed. 8 This study analyzes data from the ICGG Gaucher Registry to characterize the manifestations at the time of diagnosis of a large population of children and adolescents with nonneuronopathic GD. This description of pediatric nonneuronopathic GD should increase the recognition and earlier diagnosis of this condition in childhood, allowing for the initiation of treatment before the development of severe morbidity or irreversible disease complications.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, an inquiry at the Gaucher Registry database [2]revealed that this patient is the only nonsplenectomized patient among 1,162 treated patients to experience ERT-induced thrombocytosis. Recent data from the ICGG Gaucher Registry record only 86 patients with at least 1 episode of platelet counts ≥500 × 10 9 /l.…”
Section: Discussionmentioning
confidence: 99%
“…Thrombocytopenia of varying severity has been reported in more than 50% of Gaucher disease patients with an intact spleen because of hypersplenism. Due to bone marrow infiltration, it is even seen in 13% of patients who have been splenectomized [2]. …”
Section: Introductionmentioning
confidence: 99%
“…Half the patients are thrombocytopenic with a history of clinically significant bleeding in 42% [70]. Nevertheless, only 5 patients (8%) had undergone splenectomy (4 total), a significantly lower splenectomy percentage than usually observed among pre-ERT patients with type 1 Gaucher disease (25% -30%) [72]. This disparity may reflect the young age of the NPD-B study population because among 887 children and teenagers with type 1 Gaucher disease, only 5% reported having splenectomy [73].…”
Section: Niemann-pick Disease Types a And B (Npd-b Asm Deficiency)mentioning
confidence: 93%
“…The spleen size can be enlarged as much as 75-fold, but the median is 15.2 multiples of normal [72]. Solitary or multiple focal splenic nodules were reported present in 18.4% of patients with GD1 [95] although the prevalence may actually be greater because such nodules may not always be detected if MR imaging is restricted to T1-weighting.…”
Section: Gaucher Disease (Gd)mentioning
confidence: 99%